Influence of Ceramic Roof Tile Waste Powder as a Partial Cementitious Material on the Initial and Final Setting Times of Cement Paste - Tiara Maharani Ayu; Maryoto Agus; Intang Setyo Hermanto Nor (E3S Web of Conferences)
Kebumen Regency generates an estimated 503,242 tons of ceramic tile waste annually. We can use this waste as a cementitious material in mortar mixtures. Based on this background, the goal of this research is to determine the setting time of a cement mixture containing ceramic tile waste powder. We tested the fineness and setting time of the cement and ceramic tile waste powder mixture. We used a Blaine tool to measure the fineness parameter. In the meantime, we tested the setting time with the Vicat tool. The study encompasses both the initial and final setting times. The research results showed that the addition of ceramic tile waste powder as a cement substitute increased the initial setting time and final setting time.